STUDI FAKTOR – FAKTOR LINGKUNGAN FISIK RUMAH PENDERITA DBD DI WILAYAH KERJA PUSKESMAS PURWOKERTO SELATAN KABUPATEN BANYUMAS TAHUN 2014 - Donie Ajian Veronica; Arif Widyanto; Budi Triyantoro (Poltekkes Kemenkes Semarang, 2015)
Dengue Hemorrhagic Fever (DHF) disease is an infection disease caused by Dengue virustransmitted primarily through bites of Aedes aegypti. Based on the Purwokerto Selatan Public HealthCenter repotrs the number of dengue cases incedence from January to December 2013 recorded 92cases.The research objective was to describe physical house environment factors of DHF patients atdistrict Purwokerto Selatan Public Health Center like height of place, rainfall, ilumination, air temperatur,air humidity, kind of breeding place, and mosquito larva density (C.I, H.I, B.I, ABJ). The sample caseswere all patients with dengue in the public health center Purwokerto Selatan 2013.The research result shows from 77 patient was observation as subyek of cases DHF with agebetween 11-15 years old are 14 people (18,18%), 66,23 % are man with total 51 people, 46, 75 % arestudents with total 36 people. Height of places average are 74 meters from surface of the sea. Rainfall3.940 mm. Average of ilumination for part in the house 130 lux, part out of the house 443 lux. Average airtemperature for part in the house 31oC, part out of the house 32oC. Average air humidity part in thehouse 66%, part out of the house 62%. Total container was found are 285 container. C.I=2,45%,H.I=9,09%, B.I=9,09%, dan ABJ=90,0%.Kind of breeding place was found are basin for bath, place for clean water, vase, dispenser,refrigerator, pail, aquarium, pond, second objects, and container for drink bird. Mosquito larva density C.Iborder fill from WHO, (≤ 5%), border fill from WHO H.I (≤ 10%), B.I border fill from WHO (≤ 50%), andABJ border fill from WHO (≥ 95%) because of that be needed do restraint for mosquito larva. Give asuggestion to all people for do